IMAM SEBAGAI PEMIMPIN PUBLIK ANALISIS BIOGRAFI ZERUBABEL MENURUT KITAB EZRA DAN IMPLEMENTASINYA BAGI PEMIMPIN GEREJA MASA KINI - Paulus Kunto Baskoro (Sekolah Tinggi Teologi Arastamar Bengkulu, 2023)
Leadership is central to all church decisions and develoments. Strong leadership will bring great impact to the church. Often what happens, leaders only focus on structure and not on function. The leadership sungction will be seen from the work produced. A trus leader is a leader who always focuses on paying attention to the spiritual life and relationship of the people wirh God. Zerubbabel becomes an important part in this writing, because the writer will conduct a study of the person of Zerubabel who carried out his function of the public leaders who have a big impact on the nation of Israel. Today it is necessary to have leaders who have function of the priesthood according to the of God’s Word. This writing uses descriptive literature method. The goal is that through writing, namely First, every church leader can carry out leadership function effectively and not just structurally. Second, every church leader really pays attention to the spiritual life of the people. Third church leaders who have clear goals in developing God’s church